Brazil and the BRICS: The Trap of Short Time - Pedro Antonio Vieira; Helton Ricardo Ouriques (Journal of World-Systems Research, 2016)
In this paper we examine the BRICS by focusing on one of its member states: Brazil. More specifically, we focus on the relationship between Brazilian foreign policy under President Lula (2003-2010), U.S. hegemonic decline, and the commodity boom that provided economic resources to sustain Brazil’s position in world politics. With the world financial crisis of 2008, Lula’s belle époque came to an end. Without the abundant resources of commodity exports, Lula’s successor, Dilma Rousseff, tried unsuccessfully to combat the economic slowdown by further strengthening the economic role of the state. With this expansionist economic policy, she was elected for a second term in office, but immediately embraced the previous orthodox economic policies, what coupled with lack of support from the Congress, threw the government into crisis. As a result, not only has the political economy of Brazil re-aligned with the interests of financial capital, but also its foreign policy has returned to its historical alignment with the United States. Our contention is that the BRICS will soon be of no relevance to Brazil.